Analisis Tingkat Kesehatan Bank Perkreditan Rakyat Syariah Berdasarkan Peraturan Bank Indonesia Nomor: 9/17/PBI/2007 - Muslimin, Hamzah; Sofhian, Sofhian (Madani: Jurnal Pengabdian Ilmiah, 2020)
This study aims to determine how the analysis of the development of the soundness level of Islamic Rural Banks (BPRS) based on the Bank Indonesia Regulation Number: 9/17/PBI/2007, this study uses a qualitative approach. The population in this study is to use the BPRS financial reports from 2010-2014. The sample selection used purposive sampling technique and used secondary data. The data analysis technique uses trend analysis. This trend analysis aims to determine the tendencies or trends in the financial condition of a company in the future, either up, down or fixed. This analysis technique is usually used to analyze financial statements. This analysis is intended to determine the development of the company through the past time travel and projecting the situation from that period to the next. Research Results From the assessment of banking health and its relation to the CAMEL ratio, the Sharia Rural Bank (BPRS) has experienced an increase and decrease in the percentage due to the lack of ability of the BPRS to face the competition that occurs in the banking system which is the cause of the fluctuation in Islamic Rural Banks.